Statistical optimization of process parameters influencing the biotransformation of plant tannin into gallic acid under solid-liquid fermentation - Bibhu Prasad Panda; Rupa Mazumder; Rintu Banerjee (Wolters Kluwer Medknow Publications, 2009)
Purpose : To optimize and produce gallic acid by biotransformation of plant tannin under solid-liquid fermentation. Materials and Methods : Optimization of different process parameters like temperature, relative humidity, pH of the liquid medium, fermentation period, volume of inoculum weight of substrate influencing gallic acid production from plant tannin were carried out by EVOP factorial method. Results : Maximum gallic acid yield of 93.29% was produced at 28ΊC, 70% relative humidity, pH 6, a 72-hour fermentation period, 3 ml inoculum volume, and 25 g substrate weight, from plant tannin under solid-liquid fermentation. Conclusion : Gallic acid (3, 4, 5-trihydroxy benzoic acid), an important organic acid for synthesis of propyl gallate and trimethoprim, was produced by solid-liquid fermentation using Rhizopus oryzae NRRL 21498. Combination of Evolutionary operation, factorial design, and response surface methodology was applied successfully to elucidate the effect of different process parameters influencing biotransformation of natural tannin (powdered chebulic myrobalan fruit) to gallic acid.